Homeless cats, a societal problem - an analysis of the collaboration between cat shelters and the competent authorities in Sweden - Frida Lundmark Hedman; Malin Karlsson; Jenny Yngvesson (Frontiers in Animal Science, 2025)
In Sweden, homeless cats are primarily considered an animal welfare issue and are protected by animal welfare legislation. The 21 regional County Administrative Boards (CABs) are responsible for enforcing this legislation and acting if non-compliance is detected. According to the Swedish Animal Welfare Act, homeless cats are suffering per se, and hence the CABs must take measures to seize the cats. However, the CABs do not have any cat shelters of their own; instead, they are supposed to procure private cat shelters to handle homeless and neglected cats. This study aimed to scrutinise the collaboration between the CABs and contracted private cat shelters regarding the handling of homeless cats in Sweden. More specifically, the study examined the content and demands of these contracts, and how the cat shelters’ staff perceived this collaboration. Official documentation regarding procured cat shelters was analysed, and eight cat shelters from different counties were interviewed. Of the 21 CABs, 17 had contracts with cat shelters. The contracts varied somewhat in content but generally included demands relating to the competence of shelter staff, accessibility and lead times, documentation, equipment, and reimbursement. Most CABs also demanded that cat shelters take ownership of cats when the CAB decided. For homeless cats, this could be immediately after capture. The cat shelters were aware that they were partly being used by the CABs, i.e. they were doing some of the government’s work without full financial compensation. However, they also showed understanding for the CABs’ limited resources and were often willing to take ownership of cats early to avoid possible euthanasia decisions made by the CAB. Nevertheless, the large number of homeless cats in Sweden shows that the current system is ineffective. All relevant actors, including cat owners and the authorities, must take responsibility for their obligations.